2022
DOI: 10.22438/jeb/43/1/mrn-1868
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and population structure of Leucinodes orbonalis (Guenée), a severe insect pest of brinjal in India

Abstract: Aim: The present study was undertaken to provide valuable insights regarding population genetic structure of Leucinodes orbonalis from diverse agro-ecologies of India. Methodology: Molecular characterization of L. orbonalis populations collected from five major agro-climatic zones of India was carried out using mitochondrial cytochrome oxidase I (COI) gene. Collected specimens were subjected to DNA extractions, partial PCR amplification and sequencing of the target gene, and multiple sequence alignments. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…These results suggest that genetic flow exists between populations. Similar results were found by Padwal et al (2021) revealing a 93.13% variation within populations and 6.87% among populations, with a genetic distance of 0.004.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…These results suggest that genetic flow exists between populations. Similar results were found by Padwal et al (2021) revealing a 93.13% variation within populations and 6.87% among populations, with a genetic distance of 0.004.…”
Section: Resultssupporting
confidence: 85%
“…At the same time variation was found to be higher among groups than inside them. These differences with our study and that of Padwal et al (2021) may be due to a higher sampling per locality in our study, while the mentioned study used 150 samples worldwide, considering 17 countries. Considering the differences through an altitudinal gradient, Demirci et al (2012) proposes that altitude was not a determinant factor in the population genetic structure of Culex theileri Theobald, 1903 (Diptera: Culicidae) since genetic flow oversees maintaining connectivity between populations.…”
Section: Resultscontrasting
confidence: 84%
“…Based on the molecular characterization with RAPD markers (Deepa and Srivastava, 2011) and COI gene (Chakravarty et al, 2021), phenotyping of immature and adult stages Chakravarty et al, 2023b), and other biological traits (Chakravarty et al, 2019 and2023a), existence of sub-specific level variations among Helicoverpa armigera populations from diverse agro-ecologies of India has been deciphered. Similar studies for Leucinodes orbonalis (Padwal et al, 2022), Spodoptera litura (Ganguly et al, 2023) and Maruca vitrata (Mahalle et al, 2022) revealed genetic homogeneity for these pest species in the country. Further, Mahalle et al (2023) have also screened publically accessible expressed sequence tag resources to identify microsatellites and evaluate their suitability as DNA markers for investigating gene flow patterns among populations of M. vitrata from pigeonpea fields throughout India.…”
Section: O N L I N E C O P Ysupporting
confidence: 61%
“…A part of the mitochondrial cytochrome oxidase I (COI) gene was proposed to serve as ‘DNA Barcode’ to identify animal species based on their unique group of DNA Barcode sequences (Hebert et al., 2003 ). Therefore, ‘DNA Barcode’ sequences were compiled from several publications on the Austral‐Asian L. orbonalis (Chang et al., 2014 ; Mally et al., 2015 ; Sagarbarria et al., 2018 ; Shashank et al., 2015 ; Murali et al., 2017 ; Palraju et al., 2018 ; Karthika et al., 2019 ; Natikar et al., 2022 ; Padwal et al., 2022 ), DNA Barcode sequences available in the Barcode of Life Database and sequences not published in the literature but submitted as ‘unpublished’ to GenBank. We assembled a total of 398 sequences into a DNA alignment (Data S1 ) and used the R packages APE (Paradis et al., 2004 ) and SPIDER (Brown et al., 2012 ) as well as the FigTree v1.4.4 software (Rambaut, 2006–2018 ) to analyse the data and illustrate a neighbour‐joining tree (Figure A.1 ).…”
Section: Figure A1mentioning
confidence: 99%